Due matrimoni alle origini dello scisma anglicano? (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il contesto storico e politico della Riforma anglicana - 2. Il precedente storico: la dichiarazione di nullità del matrimonio tra Edoardo IV ed Elizabeth Woodville - 3. Il Titulus Regius - 4. Fondamento giuridico del Titulus Regius in base al diritto canonico - 4.1 (segue) Aspetti sostanziali - 4.2 (segue) Profili procedurali - 5. Sui motivi di nullità del matrimonio tra Enrico VIII e Caterina d’Aragona - 6. Il processo di nullità matrimoniale e lo scisma - 7. Conclusioni.Did two marriages cause the Anglican Schism?ABSTRACT: The Anglican schism, solemnized by the Act of Supremacy in 1534 emerged from the European Protestant Reformation that at its beginning was a movement of dissent against the Roman Church. It spread throughout Europe thanks to political and economic support of many princes who transformed it into State religion. Movement’s success is strictly linked to the intention of individual States to claim their autonomy, unfettering themselves from external influences, such as the papacy, and thus creating State’s territorial Churches. The Church of England’s schism originates from this peculiar historical and religious scenario, and has its roots in a general process to claim sovereignty of the Kingdom against any external influence. Nevertheless, someone – especially English literature, still believes that the real reason behind Anglican schism is Pope Clement VII’s refusal to declare null the marriage of Henry VIII with Catherine of Aragon and consequently preventing him from marrying Anne of Boleyn. We deemed it necessary a critical examination of the matter concerning the refusal to grant nullity to Henry VIII’s marriage, in order to determine whether the underlying cause of the Act of Supremacy was a love story that turned out badly, or other more ordinary reasons. For this purpose, we have analysed an equally resounded, but lesser known trial. It regards the declaration of nullity of the marriage between Edward IV and Elizabeth Woodville, granted few decades earlier, as it represents a significant legal/matrimonial precedent of schismatic nature. We tried to evaluate the legal legitimacy, according to matrimonial canon law, in force at that time, to evaluate whether or not justice was done.
Keywords: Varie